Fabrication and comparison between poymeric membrane with mixed matrix membrane on their prformance for O2/N2 separation - Bangga, Christabel Melanie (2012)
Development of polymeric gas separation membranes is one of the fastest growing branches in membrane technology.There have been many research made on the improvement of the performance of polymeric membranes over the recent years. However,polymeric membranes are somewhat deficient in meeting the requirements of current membrane technology. Therefore,mixed matrix membranes (MMMs),comprising of rigid permeable or impermeable particles such as zeolites,carbon molecular sieves (CMS),silica,and carbon nanotubes, dispersed in a continuous polymeric matrix presents an interesting approach for improving the separation properties of polymeric membranes.The main objective of this study is to compare polymeric membranes with mixed matrix membranes on their performance for O2/N2 separation.This research observed the effect of coating agent,silicone rubber (polydimethylsiloxane) for surface improvement for polymeric membranes and MMMs, as well as the observation of the addition and modification of zeolite 4A using silane coupling agent,3-aminopropyltrimethoxysilane (APTMOS) in the fabrication of MMMs.The fabrication of asymmetric flat sheet polymeric membranes and MMMs were prepared by using the dry/wet phase inversion technique.The prepared membranes were then coated with silicone rubber diluted in n-hexane in order to decrease the surface defects.Then, the membranes were tested using O2 and N2 gases using permeability test rig. The surface and morphology of the samples were identified by using Scanning Electron Microscopy (SEM).From the results obtained,the coating of membrane surface did enhance the selectivity of coated membranes by caulking the defects on the membrane outer surface layer.The incorporation of zeolite into polymer matrix thus somehow improved the performance of plain polymeric membrane by increasing of selectivity with high permeability.Based on the membrane performance results at 4 bar,the highest selectivity was found using coated modified MMMs at the value of 4.42,followed by coated unmodified MMMs at selectivity of 3.35, coated polymeric membranes at selectivity of 1.46, and finally uncoated polymeric membranes at selectivity of 1.44.The modification of zeolite surface using silane coupling agent improved the adhesion between zeolite and polymer which has increased the selectivity tremendously compared to the unmodified zeolite. Therefore, it is strongly agreed that coated modified MMMs is an alternative way to replace polymeric membranes for the application of membrane-based gas separation.